2015
DOI: 10.1097/qai.0000000000000380
|View full text |Cite
|
Sign up to set email alerts
|

Immunodeficiency in Children Starting Antiretroviral Therapy in Low-, Middle-, and High-Income Countries

Abstract: Background The CD4 cell count or percent (CD4%) at the start of combination antiretroviral therapy (cART) are important prognostic factors in children starting therapy and an important indicator of program performance. We describe trends and determinants of CD4 measures at cART initiation in children from low-, middle- and high-income countries. Methods We included children aged <16 years from clinics participating in a collaborative study spanning sub-Saharan Africa, Asia, Latin America and the United State… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 28 publications
4
39
0
Order By: Relevance
“…Before treatment, the ESC and the LSC both had a high proportion (47% vs. 56%) (p=0.56) of children with severe immunosuppression (<15% CD4 + %). This is consistent with a review from Koller et al who reported 70% of severe immunosuppression in children <2 years of age who started treatment in low and middle-income countries in 2010 [22]. Surprisingly, patients included in the present study had comparable mean CD4 + % independently of age at HAART initiation.…”
Section: Discussionsupporting
confidence: 82%
“…Before treatment, the ESC and the LSC both had a high proportion (47% vs. 56%) (p=0.56) of children with severe immunosuppression (<15% CD4 + %). This is consistent with a review from Koller et al who reported 70% of severe immunosuppression in children <2 years of age who started treatment in low and middle-income countries in 2010 [22]. Surprisingly, patients included in the present study had comparable mean CD4 + % independently of age at HAART initiation.…”
Section: Discussionsupporting
confidence: 82%
“…Based on an updated review (produced by Lynne Mofenson and commissioned by UNAIDS, and detailed in Annex 2 of reference [21]), on the probability of HIV transmission during pregnancy, delivery and breastfeeding, the number of children estimated to have become HIV infected was revised downward for current and historical years. Based on multiregional analyses performed by the International Epidemiologic Database to Evaluate AIDS (IeDEA), improvements were also made to more accurately reflect at what age children initiate ART [23,24]. Rather than assuming that a constant proportion of children less than age 15 years initiate ART as they become eligible as done in previous models, the current model uses age‐specific assumptions of the proportion of children starting on ART [3,20].…”
Section: Discussionmentioning
confidence: 99%
“…The Paediatric Research in Emergency Departments International Collaborative (PRE-DICT) trial showed no difference in AIDS-free survival in children >1 year; however, the median age of patients in the study was 6.4 years [35]. In lowerto middle-income countries, ART initiation in children still occurred at advanced stages of immunodeficiency, highlighting the need for improved ART access [36]. Despite evidence from the PREDICT trial, several countries in sub-Saharan Africa have recommended immediate initiation of ART irrespective of CD4 count or clinical stage, in the 5-10 year age group, because of barriers in maintaining patients in non-ART programs [36].…”
Section: Retention In Care and Antiretroviral Therapymentioning
confidence: 93%